Macroeconomic variables influencing housing prices in Vilnius - Laurinavičius, Alfredas; Laurinavičius, Antanas; Laurinavičius, Algimantas (International Journal of Strategic Property Management, 2022)
The way macroeconomic variables such as unemployment/GDP per capita/inflation/wages/internal migration influenced housing prices (nominal house prices and housing rent prices) in Vilnius in 2006–2019 has been investigated in the research. Conditions under which different macroeconomic variables could influence housing prices were established in the research. Lower unemployment, higher GDP per capita and inflation rate were all related to higher nominal house prices in Vilnius. Higher GDP per capita, wages and internal migration were positively related to housing rent prices in Vilnius. Analyzed macroeconomic variables all together explained 88 percent of variance of nominal house prices in Vilnius over the period of 2006–2019 and 80 percent of variance of housing rent prices in Vilnius over the same period.First published online 02 December 2021